Mastitis Control - David R. Bray; Jan K. Shearer (EDIS, 2009)
Revised! DS-7, a 5-page fact sheet by David R. Bray and Jan K. Shearer, describes ways to combat this complicated and expensive disease affecting dairy cows. Published by the UF Department of Animal Science, December 2008.